ANALISIS PENGARUH DISIPLIN KERJA, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. PANCA PUTRA GILANG MANDIRI MEDAN - Simbolon, Sahat; Simbolon, Dwi Maria (Jurnal Manajemen dan Bisnis, 2023)
The purpose of this study was to determine the effect of work discipline, compensation and organizational culture on employee performance at PT. Panca Putra Gilang Mandiri Medan. This research was conducted at PT. Panca Putra Gilang Mandiri Medan starts from April 2021 to August 2021. The population of this research is as many as 87 people, namely all employees who work at PT. Panca Putra Gilang Mandiri. The sample of this research is all employees of PT. Panca Putra Gilang Mandiri, totaling 87 people. This study uses the sensu method. The instrument used is a questionnaire to collect research data from the variables of work discipline, compensation, organizational culture and employee performance. The data analysis technique used is validity test, reliability test, research description analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, partial hypothesis test or t test, simultaneous hypothesis test or F test and coefficient of determination. The results of the descriptive analysis for work discipline, compensation and organizational culture are in the fairly good category , while the employee performance is in a good category. From the partial analysis, work discipline, compensation and organizational culture have a positive and significant effect on employee performance. From the simultaneous analysis of work discipline, compensation and organizational culture have a positive and significant effect on employee performance. The contribution of work discipline, compensation and organizational culture variables in improving employee performance variables was 65.9%, while the remaining 34.1% of employee performance variables were explained by other variables that were not included in the study such as recruitment, employee loyalty and so on.